Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1121/1.420101
|View full text |Cite
|
Sign up to set email alerts
|

Models and measurements of sound propagation from a point source over mixed impedance ground

Abstract: Measurements of the excess attenuation of sound from a point source over mixed impedance ground in an anechoic chamber are compared with predictions obtained from models based on (a) the semiempirical theory due to De Jong, (b) Nyberg’s theory, (c) a Fresnel-zone approximation, and (d) a boundary element code. The impedance discontinuities studied in this work are perpendicular to the source–receiver line. When there is a single discontinuity between acoustically hard and finite impedance surfaces, the De Jong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The De Jong model uses semi-empirical modifications of analytical expressions for diffraction by a rigid half-plane. Boulanger et al [88] have shown that De Jong's model gives good agreement with laboratory data for propagation over a single impedance discontinuity; however it fails if there are multiple impedance discontinuities. Lam and Monazzam [89] observed that the De Jong semi-empirical model, derived initially for a hard-to-soft discontinuity (during propagation away from the source) fails to satisfy reciprocity and modified it accordingly.…”
Section: Impedance Discontinuitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The De Jong model uses semi-empirical modifications of analytical expressions for diffraction by a rigid half-plane. Boulanger et al [88] have shown that De Jong's model gives good agreement with laboratory data for propagation over a single impedance discontinuity; however it fails if there are multiple impedance discontinuities. Lam and Monazzam [89] observed that the De Jong semi-empirical model, derived initially for a hard-to-soft discontinuity (during propagation away from the source) fails to satisfy reciprocity and modified it accordingly.…”
Section: Impedance Discontinuitiesmentioning
confidence: 94%
“…A Fresnel-zone method is used to account for discontinuous terrain in the HARMONOISE prediction scheme [80]. As has been noted elsewhere [3,88,91], a Fresnel-zone approximation, while potentially satisfactory for predicting overall broadband levels, is not useful for detailed predictions over multiple discontinuities.…”
Section: Impedance Discontinuitiesmentioning
confidence: 99%
“…[22] for a single discontinuity. Boulanger et al [23] show that De Jong model gives good agreement with laboratory data for propagation over a single impedance discontinuity; however it fails if there are multiple impedance discontinuities. Lam and Monazzam [24] observe that the De Jong semiempirical model, derived initially for a hard-to-soft discontinuity (during propagation away from the source) fails to satisfy reciprocity and modified it accordingly.…”
Section: Multiple Discontinuitiesmentioning
confidence: 91%
“…A Fresnel zone method is used to account for discontinuous terrain in the HARMONOISE prediction scheme [4]. Boulanger et al [23] propose a modification to the Fresnel zone scheme used by Hothersall and Harriot [17]. Instead of the linear interpolation of two excess attenuations, Boulanger et al [23] use a linear interpolation between the two pressure terms.…”
Section: Multiple Discontinuitiesmentioning
confidence: 99%
“…The approach decided upon was very similar to that implemented within the F ederal Highway Administration's Traffic Noise Model (FHWA TNM ®) 28,29 and is based on the work of Boulanger. 32 Specifically, the acoustically soft -ground and hard-ground effect were apportioned based on a distance-weighted coefficient. This coefficient was computed based on the ground distance associated with the acoustically hard and acoustically soft portion of the ground contained within the so -called Fresnel Ellipsoid.…”
Section: Application For Mixed Groundmentioning
confidence: 99%